The Health Benefiting Mechanisms of Virgin Olive Oil Phenolic Compounds - Lisa Parkinson (Molecules, 2016)
Virgin olive oil (VOO) is credited as being one of the many healthful components associated with the Mediterranean diet. Mediterranean populations experience reduced incidence of chronic inflammatory disease states and VOO is readily consumed as part of an everyday Mediterranean dietary pattern. VOO is rich in phenolic compounds and the health promoting benefits of these phenolics are now established. Recent studies have highlighted the biological properties of VOO phenolic compounds elucidating their anti-inflammatory activities. This paper will review current knowledge on the anti-inflammatory and nutrigenomic, chemoprotective and anti-atherosclerotic activities of VOO phenolics. In addition the concentration, metabolism and bioavailability of specific phenolic compounds will be discussed. The evidence presented in the review concludes that oleurepein, hydroxytyrosol and oleocanthal have potent pharmacological activities in vitro and in vivo; however, intervention studies with biologically relevant concentrations of these phenolic compounds are required.